2020
DOI: 10.3390/jcm9082376
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends and Risk Factors for Delayed Hospital Admission in Suspected Stroke Patients

Abstract: (1) Background: The benefit of acute ischemic stroke (AIS) treatment declines with any time delay until treatment. Hence, factors influencing the time from symptom onset to admission (TTA) are of utmost importance. This study aimed to assess temporal trends and risk factors for delays in TTA. (2) Methods: We included 1244 consecutive patients from 2015 to 2018 with suspected stroke presenting within 24 h after symptom onset registered in our prospective, pre-specified hospital database. Temporal trends were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…This was also demonstrated in numerous international studies where referrals from other medical facilities as well as awakening with symptoms lead to longer delays to hospital presentation. [ 28 , 31 , 32 ] Patients who arrived at the hospital via primary EMS calls had the shortest delays from symptom onset to hospital arrival, congruent with international data. [ 4 , 13 , 14 , 27 ] Considering the relatively quick median EMS call-to-hospital-arrival time of 1 hour and 31 minutes, it is evident that the longest delays occurred before EMS was activated.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This was also demonstrated in numerous international studies where referrals from other medical facilities as well as awakening with symptoms lead to longer delays to hospital presentation. [ 28 , 31 , 32 ] Patients who arrived at the hospital via primary EMS calls had the shortest delays from symptom onset to hospital arrival, congruent with international data. [ 4 , 13 , 14 , 27 ] Considering the relatively quick median EMS call-to-hospital-arrival time of 1 hour and 31 minutes, it is evident that the longest delays occurred before EMS was activated.…”
Section: Discussionsupporting
confidence: 66%
“…This is in contrast to other studies in HIC where time of symptom onset and weekday presentation are associated with shorter delays. [ 27 , 32 , 33 ] Anecdotally, this could be due to better access to transport or improved stroke symptom recognition with the rest of the family or support structure at home, rather than at work. Our study also demonstrated shorter symptom onset-to-hospital-arrival times in patients in the highest income category, where 80% using private transport.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of a median patient delay of 280 min was longer than that reported in other studies 8,19,29 . This could be explained by different registrations of symptom onset for wake‐up strokes and patients with reduced consciousness found by others 30 . Additionally, we included patients with minor to severe stroke.…”
Section: Discussionmentioning
confidence: 51%
“…Several studies have reported that the system delay (and the total prehospital delay) was shorter if the EMS was the first to be contacted and that the system delay was prolonged if the first contact was directed to the GP 17,19,29–31 . We used a patient delay of up to 3 h as cut‐off, as this makes arrival within the time window for reperfusion therapy reachable for the early group.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 67 studies addressing pre-hospital organizational factors associated with delay or access to ART ( Appendix A - Table A3 ). Activation of stroke code, pre-hospital notification and use of pre-hospital emergency services [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], mobile stroke units [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], implementation of specific electronic apps to insert and share clinical data with the hospital stuff [ 33 ], use of ambulance [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], telestroke [ 47 , 48 ], implementation of specific pre-hospital protocols [ 49 , 50 ], education campaigns […”
Section: Resultsmentioning
confidence: 99%